FRACTIONAL CALCULUS, SHORT HISTORY - FATIMA NAHRI, SYEDA FARRA (Innovare Journal of Sciences, 2020)
We know how to find derivatives .But it is a question that how to find derivatives if the order of differentiation to be negative or non integer. To find such types of derivatives, field of mathematics that is fractional calculus is used. Fractional order derivatives and integrals give a new dimension to mathematicson one hand and many problems in physical sciences can be expressed and solved successfully by using fractional calculus on the other hand. In this paper we discuss in brief fractional calculus.